P2X2 Receptor Expression and Function Is Upregulated in the Rat Supraoptic Nucleus Stimulated Through Refeeding After Fasting - Ivetic, Milorad; Bhattacharyya, Anirban; Zemkova, Hana (Frontiers in Cellular Neuroscience, 2019)
Magnocellular neurons in the supraoptic nucleus (SON), which synthesize and release arginine vasopressin (AVP) and oxytocin (OT), express several subtypes of ATP-stimulated purinergic P2X receptors (P2XR) that modulate neuronal activity as well as neurotransmitter and hormone release. However, the physiological impact of this modulation is not well understood. Here, we tested a hypothesis that P2XRs play a role in the sustained release of hormones from SON neurons stimulated through fasting/refeeding. We studied the effect of 2 h of refeeding after 48 h of fasting on P2XR and P2YR mRNA expression and ATP-induced presynaptic and postsynaptic responses in the SON of 30-day-old rats. Quantitative real-time PCR revealed that the expression of P2X2R and AVP mRNA was upregulated, whereas P2X4R, P2X7R, P2Y2R and OT mRNA levels were not significantly changed and P2Y1R mRNA expression was decreased. Whole-cell patch clamp recordings performed on isolated rat brain slices showed that the amplitude of the ATP-stimulated somatic current and the ATP-induced increases in the frequency of spontaneous GABAergic inhibitory postsynaptic currents were significantly higher in SON neurons from fasted/refed rats than in SON neurons from normally fed rats. No evidence was found for changes in the presynaptic effect of ATP in SON neurons not expressing somatic P2XRs. These results suggest that the increased activity of SON neurons synthesizing AVP is associated with enhanced expression of P2X2Rs on neuronal cell bodies and their GABAergic presynaptic nerve terminals.